Esterase activities in the bivalve molluscs Adamussium colbecki as biomarkers for pollution monitoring in the Antarctic marine environment: a preliminary field study - Bonacci, Stefano; Browne, Mark A.; Dissanayake, Awantha; Hagger, Josephine A.; Corsi, Ilaria; Focardi, Silvano; Galloway, Tamara S. (Marine Pollution Bulletin, 2004)
Marine environments are continuously being threatened by a large number of xenobiotics from anthropogenic sources. Even in sparsely populated and relatively pristine areas, such as Antarctica, hazardous chemicals can pose a serious environmental problem. The main aims of the present study were to (1) validate and optimize an analytical technique utilizing a microtitre-plate photometer to ascertain background levels of esterase activities in the Antarctic bivalve Adamussium colbecki, (2) carry out in situ monitoring of esterase activities to assess any potential environmental impacts of the Italian Scientific Antarctic Base "Terra Nova Bay" on the surrounding marine area. Results showed the presence of organophosphorous-sensitive cholinesterase (ChE) and carboxylesterase (CbE) activities in the gills of A. colbecki and optimal assay conditions were comparable with those found for bivalve species from temperate areas. A higher sensitivity of ChE versus acetylthiocholine activity in A. colbecki to chlorpyrifos compared to species from temperate areas may also be inferred. The in situ study indicated no differences in the environmental quality of the three study sites located around the Italian Base. © 2004 Elsevier Ltd. All rights reserved.